Therapy deserts: A call to action to address inequitable access to therapy services among pediatric orthopaedic patients - Maike van Niekerk, PhD; Kathryn Harbacheck, ACT; Chiamaka Obilo, AB; Timothy Liu, PT, DPT; Amy Weisman, PT, DPT; April Johnson, MA, CCC-SLP; Sophia Magaña, OTD, OTR/L; Karthik Balakrishnan, MD, MPH; Keith Cook, PT, DPT; Kevin Shea, MD (Elsevier, 2024)
ABSTRACT: Background: ''Food deserts'' are areas with limited access to affordable and healthy foods, disproportionately affecting low-income and ethnic-minority communities in the United States. Analogous disparities exist in other disciplines. Our interprofessional team observed ''therapy deserts" in orthopaedic and rehabilitation settings, wherein pediatric patients (particularly those with Medicaid-type insurance) appeared to lack equal access to physical therapy (PT), occupational therapy (OT), and speech-language pathology (SLP) services. Inadequate access to therapy services places patients at risk for worse outcomes. Methods: We conducted a quality improvement project to assess pediatric patients' access to therapy care in our region. We surveyed all local PT, OT, and SLP clinics identified from a comprehensive listserv maintained by pediatric therapy teams in our institution. Using a scripted questionnaire, we contacted 113 PT, 38 OT, and 82 SLP clinics external to our institution, collecting data on accepted conditions, appointment waitlist periods, and accepted insurance types. Our primary objective was to determine the percentage of clinics that accepted patients with Medicaid-type insurance. We supplemented our survey with an examination of the Area Deprivation Index for each clinic location. Results: 59 PT clinics (52%), 15 OT clinics (39%), and 36 SLP clinics (44%) completed the survey. Clinics often had limited capacity to care for medically complex conditions. Waitlist times varied, with a median wait of 1 week for PT services, 1 month for OT services, and immediate availability for SLP services. Only 14% of responding PT clinics, 53% of OT clinics, and 22% of SLP clinics accepted patients with Medicaid-type insurance. Insufficient reimbursement rates were frequently cited as the reason for not accepting Medicaid-type insurance. Waitlist times were longer for PT and SLP clinics that accepted Medicaid-type insurance compared to those that did not. Moreover, clinics that accepted Medicaid-type insurance were, on average, in more disadvantaged locations. Conclusions: Our findings suggest the existence of "therapy deserts," where limited access to therapy services is influenced by insurance type and patient complexity. These restrictions likely exacerbate existing health disparities and illustrate a systemic problem rooted in complex social drivers of health. Addressing ''therapy deserts'' requires collaborative efforts from multidisciplinary teams. Key Concepts: (1) ''Food deserts'' are areas with limited access to affordable and healthy foods that disproportionately affect low-income and ethnic-minority communities in the United States. (2) We propose that such "deserts" exist in other disciplines, including orthopaedics, wherein our interprofessional team of health care providers universally observed unequal access to therapy services-including physical therapy (PT), occupational therapy (OT), and speech-language pathology (SLP)-among pediatric patients. (3) Within our geographical region, we found only 1 in 10 PT clinics, 1 in 4 SLP clinics, and 1 in 2 OT clinics accepted pediatric patients with Medicaid-type insurance. Clinics that accepted Medicaid-type insurance were, on average, in more disadvantaged locations than those that did not. (4) The existence of "therapy deserts" likely further exacerbates existing health disparities, and requires immediate attention from orthopaedic surgeons, allied health care providers, policymakers, researchers, and the public. (5) Successfully addressing "therapy deserts" requires a multifaceted approach and may include: expanding insurance coverage for therapy services; offering financial incentives (eg, tax incentives/exemptions) to clinics providing these services; developing partnerships between non-profit and for-profit organizations; implementing innovative methods of delivering therapy services (eg, virtual appointments); upskilling local providers; and involving communities in the development of interventions. Level of Evidence: Level III